Tourism development in Kazakhstan - Ramazanova, Makhabbat (2019)
The Republic of Kazakhstan is an oil exporting country, and in the present context, it attempts to diversify its economy by developing other sectors. Among them, tourism industry has been identi ed as one of the key sectors with high potential in generating income to the country. Therefore, the Government of the Republic of Kazakhstan has given a special emphasis to tourism since the last decade through the development of tourism support strategies and programs. The overall aim of this study is to examine the tourism development potentials of the Republic of Kazakhstan during the last decade, with reference to the Shchuchinsk-Burabay resort area, located in Akmola region of northern Kazakhstan. Furthermore, the paper highlights the challenges confronting the country and provide some recommendations for authorities and tourism businesses for successful tourism development.